Zolpidem Administration and Risk of Hepatocellular Carcinoma: A Case-Control Study in Taiwan - Shih-Wei Lai; Shih-Wei Lai; Cheng-Li Lin; Cheng-Li Lin; Kuan-Fu Liao; Kuan-Fu Liao (Frontiers Media S.A., 2017)
Background/Objectives: Previous studies showed that zolpidem use could be associated with increased cancer risk, but the role of zolpidem on hepatocellular carcinoma (HCC) risk remains undetermined. The study purpose was to examine the association between HCC risk and zolpidem use in Taiwan.Methods: Using the database from the Taiwan National Health Insurance Program, we designed a case-control study which consisted of 77986 subjects aged 20 years or older with newly diagnosed HCC as the case group, and 77986 subjects without HCC as the control group, from 2000 to 2011. Ever use of zolpidem was defined as a subject who had at least a prescription for zolpidem before the index date. Never use was defined as a subject who did not have a prescription for zolpidem before the index date. The association between HCC risk and zolpidem use was determined by the odds ratio (OR) and 95% confidence interval (CI) in a multivariable logistic regression model.Results: After adjustment for confounding factors, the adjusted OR of HCC was 1.05 (95% CI 0.97, 1.13) for subjects with ever use of zolpidem, compared with never use of zolpidem. The adjusted OR of HCC was 1.01 for subjects with increasing cumulative duration of zolpidem use for every 1 year (95% CI 0.99, 1.03), compared with never use of zolpidem.Conclusion: There is no significant association between HCC risk and zolpidem use. There is no duration-dependent effect of zolpidem use on HCC risk.